STANDARDISASI EKSTRAK ETANOL BIJI BAGORE (Caesalpinia crista L.). - Ardiansa, Ardiansa; Syarif, Rezki Amriati; Waris, Risda (Makassar Natural Product Journal (MNPJ), 2024)
Bagore plant (Caesalpinia crista L.) belongs to the tribe Leguminosae and grows wild on the coast. Standardization is important to guarantee potency uniformity benefits by ensuring the concentration of active ingredients through qualitative analysis of secondary metabolites, ensuring the safety and stability aspects of extracts and increasing the economic value of extracts by various analyses such as specific and non-specific parameters. This study aims to standardization bagore seed extract (Caesalpinia crista L.) and determine the value of specific and non-specific parameters of. Samples were obtained from Binuang District, Polewali Mandar Regency, West Sulawesi Province, macerated with 96% ethanol then standardized with specific and non-specific parameters. The results of the study obtained specific parameter values as follows; organoleptic tests obtained extracts in the form of viscous, light brown in color, characteristic smell and very bitter taste; The content of soluble compounds in water is 14.361%; the content of soluble compounds in ethanol is 15.708%; positively contains flavanoid compounds, alkaloids and saponins; and the value of non-specific parameters as follows: drying shrinkage which is 0.439%; specific weight of 0.859 grams; moisture content of 2.589%; total ash content of 4.216%, insoluble ash content of acid which is 0.630%; The mold number is < 1.0 x 101 colonies/ml and the yeast is < 1.0 101 colonies/ml; lead metal contamination (Pb) is 0.003 g / g and cadmium (Cd) is 0.01 g / g. Research shows bagore seed extract (Caesalpinia crista L.) provides results according to the general standard parameters of medicinal plant extracts. Keyword : Bagore seed, Caesalpinia crista L., standardization, spesific parameters, non-spesific parameters.